Teacher Victimization in Authoritative School Environments. (2nd March 2018) - Kapa, Ryan R.; Luke, Jeremy; Moulthrop, Dorothy; Gimbert, Belinda
ABSTRACT: BACKGROUND: Victimization in schools is not limited to students. Teachers increasingly face threats and attacks from their students. An authoritative school environment, characterized by high structure and support, has been associated with lower rates of victimization. The purpose of this study was to explore the relationship between authoritative school environments and teacher victimization rates. METHODS: Researchers examined public school teacher responses (N = 37, 497) from the Schools and Staffing Survey regarding rules and issues facing the school community. Descriptive statistics were gathered, and a hierarchical regression technique was employed to assess the impact of a structured, supportive school environment on teacher victimization. RESULTS: Results indicate an authoritative school environment helped reduce rates of teacher victimization. White, female teachers are among the teachers most likely to experience violence from students. Enforcing school rules, by both teachers and administrators, is the most effective way to diminish episodes of teacher victimization. CONCLUSIONS: P‐12 school personnel should emphasize the importance of enforcing school rules and reducing negative issues, such as student truancy and apathy within each school. As high levels of structure and support reduce instances of violence, these findings have important implications for school environments and teacher health.